THE EFFECTIVENESS OF USING KIM S MEMORY GAME TO INCREASE STUDENTS VOCABULARY AT THE SECOND GRADE OF JUNIOR HIGH SCHOOL - Arleing Roring , Sintike; J. wowor, Diana; Kamagi, Sarah (Journal of English Culture, Language, Literature and Education, 2020)
The purpose of this research was to reveal the effectiveness of using Kim s memory game in increasing students vocabulary This research was pre experimental research using quantitative research with one group pre test and post test design Population of this research were students of SMP Negeri 3 Kombi and the sample were VIII grade students in academic year 2019 2020 and the total number of the sample were 15 students The data were collected through multiple choice test The data of this research were analysed statistically using mean score formula X< strong> < strong> The result of the data analysis showed that the highest score in pre test was 88 and the lowest was 40 The highest score in post test was 96 and the lowest was 70 The mean score of pre test was 65 33 and the mean score of post test was 81 86 The improvement was 16 53 from the pre test until the post test It was indicated that the used of Kim s Memory game was effective to improve students Vocabulary < p>